Conversion of poultry litter into class A biosolids using autothermal thermophilic aerobic digestion: A remedy for solid waste management. Issue 1 (11th January 2016) - Sridevi Dhanarani, T.; Shankar, C.; Prakash, P.; Poornima Priyadharshani, T. K.; Thamaraiselvi, K.
Abstract : Purpose: – The purpose of this paper is to minimize environmental problems related to raw poultry manure application by stabilizing its nutrient and organic matter (OM) content. This can be achieved by prior digestion before its application to agricultural soils. Design/methodology/approach: – In the present study, changes in physicochemical and microbial properties of poultry litter were studied in order to evaluate the suitability of using the digested (stabilized) product for soil amendment. The poultry litter was digested in autothermal thermophilic aerobic digestor (ATAD) where organic solids were degraded and the heat released during the microbial degradation was used to maintain the thermophilic temperatures ( < 50ºC) at a hydraulic retention time of about 3 d. Findings: – Results of this study showed that the poultry litter undergoes physicochemical and microbial changes similar to other digestion systems; these changes include self-heating, relative increase in Cu, Zn, Fe, Mn, P, K and NO3 -N and decrease in microbial population numbers, C, OM and NH4 -N contents. Originality/value: – ATAD is an effective method for the conversion of poultry litter into organic fertilizer, which can be readily applied to the agriculture land. ATAD is an eco-friendly, cost effective method which also reduces the length of stabilization.